Evaluation of the European Union regions convergence regarding innovation - Markowska, Małgorzata; Strahl, Danuta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
The paper presents an attempt to estimate sigma convergence (a-convergence) occurring in the European space at NUTS 2 level with reference to innovation. Following sigma convergence hypothesis, assuming that the spatial diversification of European regional space for variables illustrating regional innovation presents a mitigating tendency, while in the distinguished, homogenous groups, regarding the level of attributes illustrating innovation, convergence processes will be much more noticeable than in the global regional space. The research objective was carried out in three stages covering Input and Output regional innovation indicators construction, classification of the European regional space into groups of regions with regard to values of Input and Output innovation indicators by means of positional statistics application, as well as measurement and estimation of sigma convergence processes at regional level. The conducted analyses cover the period of 1999-2008, the research objects represent EU regions at NUTS 2 level (265 out of 271) and Eurostat data bases constitute the source of statistical data
Argumenta Oeconomica, 2012, Nr 1 (28), s. 41-68
Keywords: innovation convergence; EU NUTS 2 regions; konwergencja; innowacje; rozwój regionalny; klasyfikacja NUTS